(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
Premature child mortality remains a pressing public health issue in rural, economically disadvantaged areas of Nepal. This study explores socio-demographic determinants of child mortality in the Kumal community of Gandaki Province. A cross-sectional survey of 322 mothers aged 15-49 analyzed key factors such as maternal age, family size, parental education, food security, and father’s employment status. Findings indicate that older maternal age (34-49 years) correlates with higher mortality rates (χ2 = 18.96, p = 0.021). Larger family size, particularly with three or more children, increases mortality (χ2 = 6.68, p = 0.033). Lower paternal education levels are also linked to higher mortality (χ2 = 15.37, p = 0.002). Food insecurity exacerbates risk, with insufficient food increasing death rates (χ2 = 4.319, p = 0.028). Additionally, the absence of fathers due to migration further raises mortality risks (χ2 = 12.719, p = 0.049). However, the sex of the last child and the household head did not significantly impact mortality. Qualitative data support these findings, emphasizing the need for improved prenatal care, educational programs, food security initiatives, and support for families affected by migration.